2022
DOI: 10.1056/nejmoa2206485
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of an Extravascular Implantable Cardioverter–Defibrillator

Abstract: BACKGROUNDThe extravascular implantable cardioverter-defibrillator (ICD) has a single lead implanted substernally to enable pause-prevention pacing, antitachycardia pacing, and defibrillation energy similar to that of transvenous ICDs. The safety and efficacy of extravascular ICDs are not yet known. METHODSWe conducted a prospective, single-group, nonrandomized, premarket global clinical study involving patients with a class I or IIa indication for an ICD, all of whom received an extravascular ICD system. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 39 publications
3
59
0
2
Order By: Relevance
“…Recently, the first results of the EV-ICD CE/investigational device exemption trial reported the outcomes of 299 patients that received a fully implanted device. 32 After FU for at least 6 months for all patients, the 2 predefined primary endpoints were both met. The efficacy of the defibrillation testing for induced VAs was 98.7%, which well exceeded the 84% target that was set based on prior TV-ICD and S-ICD trial outcomes.…”
Section: The Substernal Ev-icd Strategymentioning
confidence: 99%
“…Recently, the first results of the EV-ICD CE/investigational device exemption trial reported the outcomes of 299 patients that received a fully implanted device. 32 After FU for at least 6 months for all patients, the 2 predefined primary endpoints were both met. The efficacy of the defibrillation testing for induced VAs was 98.7%, which well exceeded the 84% target that was set based on prior TV-ICD and S-ICD trial outcomes.…”
Section: The Substernal Ev-icd Strategymentioning
confidence: 99%
“…Other EVDs that have been developed and are currently being studied clinically are: extravascular ICD (EV-ICD), an ICD with a substernal epicardial lead; modular cardiac rhythm management (mCRM) system, consisting of an S-ICD and LP that can wirelessly communicate to provide anti-tachycardia pacing; and dual-chamber LP, consisting of right atrial and right ventricular LPs that communicate wirelessly. Only preclinical or short-term data on these devices are available [14][15][16]. At this rate of development, many new EVDs will be available for clinical studies in the next decade.…”
Section: The Era Of Extravascular Devicesmentioning
confidence: 99%
“…This emphasises the popularity of EVDs in the Netherlands, and possibly, additional information about these devices can be collected retrospectively. Dutch hospitals have been involved in many of the early EVD studies, and presently, clinical studies with the mCRM system and dual-chamber LP are led by a Dutch hospital [14,[17][18][19][20]. Hence, combining Dutch data on EVDs will provide a unique opportunity to describe long-term safety and efficacy.…”
Section: Dutch National Evd Registrymentioning
confidence: 99%
“…21,22,23 To that end, substernal EV-ICD leads (Medtronic Inc, Minneapolis, MN) have been developed. Crozier et al 24 reported successful substernal implantation in 299 of 316 subjects (95%) with no procedural complications observed. Shock termination of induced ventricular arrhythmias was successful in 298 of 302 subjects (98.7%) when connected to a custom EV-ICD pulse generator (Medtronic, Inc, Minneapolis, MN) placed into a left posterior-lateral pocket.…”
Section: Introductionmentioning
confidence: 98%